Drawdown flushing in a chain of reservoirs—Effects on grayling populations and implications for sediment management - Walter Reckendorfer; Hannes Badura; Claudia Schütz (Ecology and Evolution, 2019)
Abstract We used an information theoretic approach to assess the effects of an ecologically adjusted sediment management scheme on grayling (Thymallus thymallus L. 1758) populations. Additionally to reservoir operation, candidate models included a variety of parameters and processes that may influence grayling populations such as flow, temperature, density dependence, and bird predation. Population parameters analyzed included total densities, young of the year numbers, and larval densities. These analyses were supplemented by a characterization of sediments and sedimentation patterns in the reach. Investigations were carried out in six sites affected by flushing and in one control site. A total of thirteen flushing operations have been undertaken within the study period leading to considerable remobilization of fine sediments and gravel. Due to seasonal and hydrological restrictions, not every flood could be used for flushing. These limitations led to an interrupted management throughout the chain of reservoirs as well as to long time intervals between flushing events with possible effects on spawning habitat quality. None of the investigated population parameters was affected by flushing, and thus, the study generally supports the current reservoir management scheme. Our analyses revealed the magnitude and timing of high water events, temperature, and density‐dependent effects, that is, population densities the year before, as the most influential variables for grayling population dynamics in the investigated stretch. The siltation of reservoirs is a significant problem for reservoir storage, flood protection, river deltas, and coastal zones. Its management—which is inevitable to safeguard river deltas and secure flood protection—poses also the challenge to safeguard riverine ecosystems below reservoirs. Based on our experience, we propose a periodic flushing regime in concordance with the hydrograph thereby mimicking the timing, magnitude, frequency, and duration of natural SSC pulses and gravel transport. This flushing regime minimizes adverse downstream environmental impacts and maximizes benefits.